PSYCHOLOGICAL ANALYSIS OF MARTIAL JOURNALIST’S PROFESSIONAL ACTIVITY - Balaklytskyi, Maksym; Kuryliak, Valentyna (Brazilian journalism research, 2020)
This article addresses the issue of social orders for martial journalists in the context of Joint Forces Operation in the territory of Ukraine, as well as the necessary and growing need for journalists to use their own psychological resources correctly under stressful working conditions. This article draws a distinction between martial and military journalism, reveals the main components of the psychological aspect of a martial journalist’s professional activity and delineates research substantiated by scientific evidence. Martial journalism entails the journalist going in the area of hostilities; in military journalism, conversely, the journalist can write from other parts of the country where there are no hostilities. The emphasis is put on the fact that Ukrainian researchers do not pay attention to the psychological health of a martial journalist with state education, in contrast to a military specialist. The authors emphasize that the psychological disfunctions of the martial and military journalists arise because of the specialists who monitor and distribute a large amount of destructive information in the Mass Media. The psychology of martial journalists was researched using the interviewing method and focused on the psychological and socio-communicative portrait of their personalities. It distinguished between the positive and negative components of their profession and suggested a list of preventive actions to minimize the influence of their activity on their psychological health. Este artigo discute a questão das ordens sociais para jornalistas marciais no contexto da Operação de Forças Conjuntas no território da Ucrânia, bem como a crescente e imperiosa necessidade desses jornalistas utilizarem corretamente seus próprios recursos psicológicos sob condições de trabalho estressantes. Faz uma distinção entre jornalismo marcial e militar, revela os componentes principais do aspecto psicológico da atividade profissional dos jornalistas marciais e realiza uma pesquisa substanciada por evidência científica. O jornalismo marcial implica em jornalistas indo a áreas de hostilidade. Já no jornalismo militar, o jornalista pode escrever de outras partes do país onde acontecem as hostilidades. A ênfase é colocada no fato de que os pesquisadores ucranianos não dão atenção à saúde psicológica do jornalista marcial com educação estatal, em contraste com o que acontece com o especialista militar. Os autores enfatizam que as disfunções psicológicas dos jornalistas marciais e dos jornalistas militares surgem por conta da atividade desses especialistas, que monitoram e distribuem uma grande quantidade de informação destrutiva nos meios de comunicação de massa. A psicologia dos jornalistas marciais foi estudada por meio do método de entrevista e se concentrou no perfil psicológico e sociocognitivo de suas personalidades. Distinguiu-se entre os componentes positivos e negativos da profissão e foi sugerida uma lista de ações preventivas para minimizar a influência de suas atividades na saúde psicológica. Este artículo aborda el tema de las órdenes sociales para periodistas marciales en el contexto de la Operación de las Fuerzas Conjuntas en el territorio de Ucrania, así como la necesidad imperiosa y creciente de que los periodistas utilicen correctamente sus propios recursos psicológicos por las condiciones de trabajo estresantes. Este artículo establece una distinción entre periodismo marcial y militar, revela los componentes principales del aspecto psicológico de la actividad profesional de un periodista marcial y delinea la investigación respaldada por evidencia científica. El periodismo marcial corresponde al periodista que acude al área de las hostilidades; en el periodismo militar, por el contrario, el periodista puede escribir desde otras partes del país donde no hay hostilidades. Se hace hincapié en el hecho de que los investigadores ucranianos no prestan atención a la salud psicológica del periodista marcial con educación general, en contraste con un especialista militar. Los autores enfatizan que las disfunciones psicológicas de los periodistas marciales y militares surgen debido a los especialistas que monitorean y distribuyen una gran cantidad de información destructiva en los medios de comunicación. La psicología de los periodistas marciales fue abordada mediante el método de entrevista y se centró en el perfil psicológico y socio-comunicativo de sus personalidades. Se distingue entre los componentes positivos y negativos de su profesión y se sugiere una lista de acciones preventivas para minimizar la influencia de su actividad en su salud psicológica.